Role Of Piezosurgery in Oral and Maxillofacial Surgery- A Review - P, Dhanalakshmi; Balakrishnan, R. (Journal of Neonatal Surgery, 2025)
Piezo surgery enables controlled cutting of hard tissues by employing modified ultrasonic vibration. Sensitive hard constructions can be cut effectively and with incredible accuracy, without obliteration of delicate soft tissue. We have discovered this gadget to be valuable when the precise cutting of thin bones is fundamental. Nonetheless, it is of just restricted use in cutting thick bones and in regions with restricted access. This overview summarises current research and involvement in piezo surgery, a promising, meticulous, and delicate tissue-saving framework for bone cutting based on ultrasonic micro-vibrations. Delicate tissue protection, optimal visibility in the operating room, less blood loss, reduced vibration and noise, assurance of tooth structure, and increased patient comfort are some of the key advantages of piezo surgery